The Place of Negotiation and Protocol in a Trade War: A Case Study of U.S.-China Trade Relations - Gakpetor, E.M. (University of Ghana, 2020)
This study is intended to provide information on the trade war between the U.S and China. It addresses negotiation and protocol as diplomatic tools used to ease tensions amongst states at the height of the ongoing economic conflict. It analyses the issues raised from the trade dispute between the U.S. and China and highlights the crucial use of negotiation, which is the key function in diplomacy, and acts as a form of soft power to achieve national interest. The methodology applied included academic research based on qualitative analysis as well as quantitative research in the form of expert interviews. The thesis further explores the consequences of the trade war in the international system as well as the challenges associated with diplomacy between Washington and Beijing. The results show that the trade war between U.S and China do not only affect the parties involved, but also other states, non-state actors and businesses holding trade and diplomatic relations with the U.S and China such as WTO. States can use a variety of strategies to mitigate the negative effects of the ongoing trade war. This study adds new insights to the existing literature on the trade war between the U.S. and China, diplomacy and its effects on long term relationships within the international system.
MA. International Affairs
Keywords: Trade war; WTO; China; U.S; Tariffs; Negotiation; Protocol; Digital Diplomacy; Twitter; Foreign Policy; Globalization